2021
DOI: 10.1002/anie.202012681
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Chirality of an Achiral Cucurbit[8]uril‐Based Supramolecular Organic Framework for Chirality Induction in Water

Abstract: Chiral framework materials have been developed for many applications including chiral recognition, chiral separation, asymmetric catalysis, and chiroptical materials. Herein, we report that an achiral cucurbit[8]uril‐based supramolecular organic framework (SOF‐1) with the dynamic rotational conformation of tetraphenylethene units can exhibit adaptive chirality to produce M‐SOF‐1 or P‐SOF‐1 with mirror‐image circular dichroism (CD) with gabs≈±10−4 and circularly polarized luminescence (CPL) with glum≈±10−4 indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 79 publications
0
63
0
Order By: Relevance
“…Based on previous reports, M-TPE and P-TPE show positive and negative Cotton effects from long to short wavelengths, respectively. [22,24] Therefore, in these cases, L-Phe induces an M rotational conformation of the TPE units in the SOF to produce M-SOF-1, while D-Phe induces a P rotational conformation of the TPE units in the SOF to produce P-SOF-1 (Scheme 1 b and Figure 3 d). The mirror-image CD spectra confirmed that the adaptive chirality of SOF-1 with a P or M rotational conformation of the TPE units can be induced by enantiomers when the enantiomers are encapsulated inside the cavities/pores of SOF-1, respectively.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous reports, M-TPE and P-TPE show positive and negative Cotton effects from long to short wavelengths, respectively. [22,24] Therefore, in these cases, L-Phe induces an M rotational conformation of the TPE units in the SOF to produce M-SOF-1, while D-Phe induces a P rotational conformation of the TPE units in the SOF to produce P-SOF-1 (Scheme 1 b and Figure 3 d). The mirror-image CD spectra confirmed that the adaptive chirality of SOF-1 with a P or M rotational conformation of the TPE units can be induced by enantiomers when the enantiomers are encapsulated inside the cavities/pores of SOF-1, respectively.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…The X-ray structure of 1 exhibits a propeller-like conformation with racemic P-and M-rotation of the TPE units in the crystalline state (Figure 3 a and Table S4). [24] As expected, 1 did not exhibit any obvious Cotton effect at different concentrations (1.0 mM-1.0 mM) and temperatures (283-333 K) in water and in different solvent systems (e.g., acetone, dioxane, EtOH, MeCN, MeOH, and THF), respectively, indicating that the TPE units in free 1 adopt racemic rotational conformation in the solution state and their homodirectional rotational (P or M) conformation cannot be easily induced and stabilized in the aggregation state or under low temperature ( Figures S27-S29). Similarly, SOF-1 did not show any obvious Cotton effect under different conditions in water or other solvents, indicating that the TPE units in the framework also adopt a racemic rotational conformation in the solution state, and their homodirectional rotational conformation (P or M only) cannot be easily induced and stabilized in the supramolecular assembly ( Figures S27-S29).…”
Section: Adaptive CDmentioning
confidence: 99%
“…Analysis of the crystal structure suggests that 1-H is a chiral supramolecular organic framework [32], which entails the self-assembly of homo-chiral (right-helix) tubes derived from the achiral semi-rigid tetra-acids being assembled via different hydrogen bond motifs. It has been confirmed in a kinetic model that an achiral artificial assembly system could spontaneously produce chirality [33].…”
Section: Spectroscopymentioning
confidence: 99%
“…The development of chiral materials has attracted great attention to their potential applications in the pharmaceutical, 1 agricultural, 2 chemical and biological elds. [3][4][5][6] As emerging chiral materials, chiral crystalline porous materials (CPMs) including metal-organic frameworks (MOFs), [7][8][9][10] covalentorganic frameworks (COFs) [11][12][13] and supramolecular-organic frameworks (SOFs) [14][15][16] possess high specic surface area, well-dened pores and variable chemical functionalities. Chiral CPMs have been rapidly expanded in enantiomer separation, [17][18][19][20][21][22] asymmetric catalysis, [23][24][25][26] nonlinear optics, 27 circularly polarized luminescence (CPL), 28,29 drug delivery 30,31 and chiral sensing.…”
Section: Introductionmentioning
confidence: 99%